A Contrastive Study of Relational attributive Clauses in Narrative Texts in English and Persian Based on Halliday (2004). (24th June 2015) - Kaffashi, Mahvash; Gowhary, Habib; Jamalinesari, Ali; Azizifar, Akbar
Abstract: The present study aimed at comparing English and Persian narrative texts in terms of manner of expressing of relational attributive clauses based on (Halliday, 2004 ). Accordingly, it incorporated a corpus of 400 clauses: 200 from English and 200 in Persian in order to find out the possible similarities and differences regarding three components of Halliday's "transitivity process", namely: the process, participants and circumstances. Relational clauses in English system are classified into three main types: 'intensive', 'possessive', and 'circumstantial'; each one has its own sub-categories: 'attributive' and 'identifying'. Frequencies and percentages of linguistic data were calculated for attributive relational clauses by using descriptive and inferential analysis. The analysis showed overall similarities across both English and Persian regarding relational attributive clauses. However, some differences were found in terms of manner of expressing, the position and number of participants, and the kind of processes. Although the employed statistical operations showed that these differences are not statistically significant.